RESEARCH OF DISPERSED THREE-COMPONENT SYSTEM AS A BASIS FOR STUFFED MASS WITH POULTRY MEAT AND VEGETABLE HYDROBIOTS - HIRENKO, Nataliia; KRAMARENKO, Dmytro (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Proper nutrition of Ukrainians is one of the most important problems of today, which shapes the health and well-being of the nation as a whole. In a rational diet a special role is played by the creation of new, balanced in composition products that are enriched with deficient functional components - minerals, vitamins, dietary fiber. Analysis of the publications of domestic and foreign scientists shows the relevance of such a direction of creating new functional products as expanding the range of multicomponent stuffed mass with a variety of raw materials of animal and vegetable origin.According to scientific studies, the value of yield strength (YS) in the case of a change in the moisture content of minced sausages by 1% changes by 10… 15%, while the numerical values of other properties (viscosity, elasticity) change slightly. Thus, yield strength is a parameter by which you can effectively control the quality characteristics of minced meat.Fat retention capacity (FRC) is a technological characteristic that is important during all stages of the technological process of production of finished meat products and semi-finished products and is the ability of the system to adsorb fat balls on the surface and convert some fat into bound state. The ability of minced meat to bind moisture strongly depends on the degree of dispersion of the particles and the moisture-binding capacity (MBC).According to theoretical studies, taking into account the traditional trends of Ukrainian cuisine, the authors chose the main mass components to create minced meat with poultry and vegetable hydrobionts, these were - minced chicken, boiled beans and onions.The aim was to study an important rheological characteristic of minced meat - changes in the YS of dispersed systems, to create multicomponent stuffing. The aim of the study was also to determine the patterns of changes in MBC and FRC three-component model systems during the introduction of different concentrations of components.The paper presents the results of experimental studies of rheological and physicochemical properties of dispersed systems for creating minced meat with poultry and plant aquatic organisms. The dependences of the main rheological indicator for the stuffing system - the yield strength. Data on the moisture-binding and fat-retention capacity of the three-component polydisperse system were also obtained. Changes of the specified indicators from change of a parity of components are investigated.
Keywords: disperse system; shear stress; forcemeat mass; artificial neural network